Identification and Evaluation of Decisive Factors in the Growth of Automobile Industry of Pakistan - Rasheed, Rukhsana; Ishaq, Mazhir Nadeem; Malik, Fahad (iRASD Journal of Economics, 2022)
Pakistan’s automobile industry is small in Asia but its growth is the fastest in this region. This industry contributes 30 billion rupees to national exchequer through taxes and contributes around 2.8 percent in GDP. Hence, it is imperative to study the economic factors that are responsible for influencing this industry in this country. The present study is a quest in this domain. Economic factors that determine car sales such as GDP growth, CPI inflation, interest rate, exchange rate, unemployment rate, and fuel prices are used. The period of this study is from 1999-2021. ARDL modeling approach is used to test and estimate the potential cointegrating relationship between the aforementioned variables. Results of this study showed that car sales are affected by changes in the interest rate and unemployment rates in the short run. Factors such as GDP growth, CPI inflation, unemployment rate, and petrol prices significantly affect the car sales in the long run. The performance of automobile industry may be improved by open up domestic market to cut the import bill and to protect the local industry from foreign competition for the benefit of consumers.